Communication and assessment of pain in hip fracture patients with dementia - experiences of healthcare professionals at an accident and emergency department in Sweden - Nail Seffo; Eric Hamrin Senorski; Olof Westin; Eleonor Svantesson; Ferid Krupić (Medicinski glasnik, 2019)
Aim: To describe the experience of healthcare professionals in assessing pain and communication in patients with hip fractures and dementia in an emergency department. Methods: Data were collected through focus group interviews using open-ended questions, following an interview guide and qualitative content analysis. Twenty one registered nurses participated in the interviews, five male and 16 female, aged 26 to 55 years. Results: The analysis of the interviews resulted in three main categories: "Arrival at the emergency department", "Hip track" and "Handover to the ward", including a number of subcategories. All nurses reported that the assessment of pain and communication with patients with dementia and hip fractures was a complex process. A great deal of stress, fast and brief communication, quick decisions and quick treatments in assessment of pain were only some of the difficulties the nurses emphasized. They also suggested a whole series of improvements for those patients. Conclusion: The situation of patients with hip fracture and dementia on the emergency department and healthcare professionals who communicate and assess their pain can be said to be untenable. The care environment in the emergency department is not adapted to patients and can of course depend on several factors. To meet the needs of the future and increased numbers of those patients, some improvements such as more extensive research and more studies on the experiences of both the patients and healthcare professionals are required.
Keywords: dementia; Emergency Department; experiences; hip fracture; qualitative research; staff